Effect of Audit Tenure and Auditor Switching on Audit Delay with Auditor Specialization as Moderating Variable - Andri Yeanne Colson Tani; Chandrarin Grahita; Zuhro Diana (Green Publisher Indonesia, 2022)
The purpose of this study was to determine the effect of audit tenure and auditor switching on audit delay with auditor specialization as a moderating variable. This study is a quantitative study using secondary data with a sample of 23 consumer goods sub-sector companies listed on the Indonesia Stock Exchange (IDX). The data collection method is done by accessing the company's financial statements published by the Indonesia Stock Exchange. The data obtained were then processed using SPSS. This analysis includes classical assumption test (data normality test, multicollinearity test and heteroscedasticity test), statistical test (F test, t test and R2 test) and moderating regression analysis (MRA). Based on the results of the tests carried out, it shows that the F test of the multiple linear regression equation model is appropriate (Fit) that there is a significant effect between audit tenure and auditor switching on audit delay. While the t test, audit tenure has no significant effect on audit delay, audit switching has a significant effect on audit delay, auditor specialization as a moderating variable cannot moderate or weaken the relationship between audit tenure and audit switching.